Az EGTC alapítás kihívásai a hármashatár térségében : a Banat-Triplex Confinium EGTC - Soós, Edit (Közép-Európai Közlemények, 2012)
The European Union created an opportunity for members to establish EGTCs, bodies with legal personality in 2006 to facilitate the cooperation of national, local and regional players and the efficient use of Union’s resources. Revision process of the EGTC Regulation (1082/2006/EC) gives an opportunity to examine the conditions for elaboration of development and codification propositions of EGTCs on the formation of Banat-Triplex Confinium with Hungary and Romania full member-ship, Serbia as observer member, and to give a new legal bases The criteria for approval by national authorities are specified, a simplificaton of procedures and a limited time for examinaton proposed. Hungarian experience from the setting up of EGTC shows the three month period for approval by a Member State has rarely been respected.